2019
DOI: 10.1111/febs.15001
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN expression is stimulated by cytosolic MtDNA released from pneumolysin‐damaged mitochondria via the STING signaling pathway in macrophages

Abstract: Pneumolysin (Ply), a major virulence factor of Streptococcus pneumoniae (S. pn), affects the immunity of host cells during infection. It has been reported that Ply is involved in S. pn standard strain D39‐induced interferon‐β (IFN‐β) expression; however, other findings suggest that recombinant Ply protein is incapable of triggering IFN‐β expression. Here, we demonstrated that purified Ply was capable of initiating oxidative damage to mitochondria, resulting in the subsequent release of mitochondrial deoxyribon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…Second, however, leakage of mitochondrial DNA from damaged mitochondria in stressed or dying cells is also a potential ligand for STING/cGAS (49)(50)(51). Since Spn invasion causes cell stress and death, DNA from damaged mitochondria or dying cells would be another potential trigger of the IFN response during invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Second, however, leakage of mitochondrial DNA from damaged mitochondria in stressed or dying cells is also a potential ligand for STING/cGAS (49)(50)(51). Since Spn invasion causes cell stress and death, DNA from damaged mitochondria or dying cells would be another potential trigger of the IFN response during invasion.…”
Section: Discussionmentioning
confidence: 99%
“…100 Interestingly, in the context of infection, there is an escape of mtDNA into the cytoplasm, where it activates cGAS-mediated type I interferon generation, conferring broad pathogen resistance. [101][102][103] However, these mtDNA-induced cGAS-mediated antiviral responses are suppressed by apoptotic caspases. 104,105 Apart from aforementioned mechanisms, cGAS is also regulated by the ionic environment.…”
Section: Compartmentalizationmentioning
confidence: 99%
“…101 An in vitro study showed that pneumolysin could initiate oxidative damage to mitochondria, resulting in the subsequent release of mtDNA, which mediates IFN-β expression in macrophages. 102 COVID-19 caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly spread to produce a global pandemic. 147 In patients with COVID-19, levels of 14 cytokines are increased; among them, CXCL10, CCL7, and IL-1 receptor antagonists are significantly higher in severe cases and are associated with increased viral load, loss of lung function, lung injury and a fatal outcome.…”
Section: Lung Inflammation and Fibrosismentioning
confidence: 99%
“…The cGAS-STING pathway protects against infections with viruses, bacteria, and protozoan parasites by sensing pathogenic DNA, infection-induced mitochondrial damage, bacterial proteins, virulence factors and metabolites, and bacteria-derived cyclic dinucleotides (CDNs) (79)(80)(81)(82)(83)(84). Meanwhile, infected cells transactivate the cGAS-STING pathway in bystander cells via the cell-to-cell transmission of cGAMP or the release of extracellular vesicles (EVs) (85)(86)(87)(88)(89).…”
Section: The Cgas-sting Pathway In Stressed Hematopoiesis Infectionmentioning
confidence: 99%
“…Activation of the cGAS-STING pathway may promote the myeloid-biased differentiation of HSPCs to enhance the anti-infection reservoir of the immune system. However, it should bear in mind that the activation of the cGAS-STING pathway may also increase the vulnerability to or severity of infections through dampening adaptive immunity, exacerbating inflammation or facilitating pathogen replication, survival, and infection (81,(108)(109)(110)(111)(112)(113).…”
Section: Translational Implicationsmentioning
confidence: 99%